The wars of the texts. - Elam, Keir (Shakespeare Studies (Rosemont Publishing & Printing Corporation), 1996)
Reviews the books `The Semiotics of Performance,' by Marco de Marinis, translated by Aine O'Healy and `The Semiotics of Theater,' by Erika Fischer-Lichte, translated by Jeremy Gaines and Doris L. Jones.